2016
DOI: 10.11113/ijbes.v3.n1.109
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to assess the Urban Management Performance of Municipalities in Sri Lanka

Abstract: Urbanization tends bring out a number of problems, such as inadequate housing and urban services, increase land prices and construction costs, propagation of slums, pollution and deterioration of the urban environment. Currently, spatial development activities focusing on major cities of Sri Lanka are demanding urban infrastructure and services where municipalities are facing challenges on provision of the infrastructure and proper urban management too. This study seeks to identify the relevant criteria, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…In one study, the technique was used to better understand agricultural standardization in peach orchard ecosystems using green indicators such as atmospheric environment, irrigation, soil, seedling quality, and the influences of living conditions on peach orchard growth [36]. Likewise, the technique was used to investigate urban government effectiveness in Sri Lanka [37]. Furthermore, 13 limited indicators out of 33 deemed significant environmental sustainability indices in the urban industry from Chinese cities were studied between 2005 and 2017.…”
Section: A Full Permutation Polygon Synthetic Indicator Methods (Fppsi)mentioning
confidence: 99%
“…In one study, the technique was used to better understand agricultural standardization in peach orchard ecosystems using green indicators such as atmospheric environment, irrigation, soil, seedling quality, and the influences of living conditions on peach orchard growth [36]. Likewise, the technique was used to investigate urban government effectiveness in Sri Lanka [37]. Furthermore, 13 limited indicators out of 33 deemed significant environmental sustainability indices in the urban industry from Chinese cities were studied between 2005 and 2017.…”
Section: A Full Permutation Polygon Synthetic Indicator Methods (Fppsi)mentioning
confidence: 99%
“…During research that was conducted in order to investigate the management of municipalities in three regions of Sri Lanka using the FPPSI method, the results showed that the combined index in none of the municipalities of the three regions did not reach a high or very high level (Ranasinghe, Amarawickrama et al, 2016).…”
Section: Intoductionmentioning
confidence: 99%